Challenges and Way Forward for Establishing Population Based Cancer Registry in Nepal - Subedi, Ranjeeta; Dhimal, Meghnath; Budukh, Atul; Gyawali, Pradeep; Jha, Anjani Kumar (Journal of Nepal Health Research Council, 2020)
Population Based Cancer Registry plays a crucial role in cancer control through identifying cancer incidence, mortality, pattern and trends over time in a particular population. The registry is in a very infancy stage in Nepal. During the process of establishing Population Based Cancer Registry in Nepal, the major challenges include adequate coverage of the cases, high cost of registration, sustainability along with expansion of the registry to other regions and non-linkage of Hospital Based Cancer Registry with Population Based Cancer Registry. However, the approach of mobilization of field enumerators at the end of year once had increased coverage of the cases. Similarly, the linkage of Population Based Cancer Registry with the existing Health Management and Information System will help in developing sustainable Population Based Cancer Registry and also provides an opportunity to increase coverage and expand it to other districts as well.Keywords: Challenges; Nepal; population based cancer registry; way forward